Developing Toonly-Based Animated Videos for Teaching Pre-Intermediate Japanese Grammar Based on Minna no Nihongo Shokyū II - Kadek Eva Krishna Adnyani; Gede Satya Hermawan; Yeni Yeni; I Kadek Antartika; Irvina Restu Handayani (KIRYOKU, 2026)
This study aims to develop Toonly-based animated videos to support the teaching of pre-intermediate Japanese grammar (Bunpō Shōchūkyū) in Indonesia and to evaluate their feasibility. The research employed the Multimedia Development Life Cycle (MDLC), consisting of six stages. The six stages are concept, design, material collection, assembly, testing, and distribution. A total of twelve animated instructional videos were developed based on grammar points from Chapters 38 to 49 of Minna no Nihongo II. The feasibility testing involved an alpha test dan beta test. Alpha test conducted by a media expert and a content expert. Beta test conducted by the course lecturer and six second-semester students from the Japanese Language Education Study Program at Universitas Pendidikan Ganesha. Data were collected through mixed-format questionnaire and semi-structured interviews. The media expert gave a score of 57.75 (Excellent), while the content expert gave 50.25 (Good). The beta test conducted by the lecturer yielded a score of 109 (Excellent), and the small-group test yielded 106.6 (Good). These results indicate that the developed animated videos are feasible and suitable as supplementary learning materials for teaching Bunpō Shōchūkyū using Minna no Nihongo II at Universitas Pendidikan Ganesha. Overall, these findings highlight the potential of animation-based media to make Japanese grammar learning more engaging, accessible, and meaningful for students.